A portable paper-based aptasensor for simultaneous visual detection of two mycotoxins in corn flour using dual-color upconversion nanoparticles and Cu-TCPP nanosheets. (15th March 2023) - Lin, Xianfeng; Li, Changxin; Tong, Xinyu; Duan, Nuo; Wang, Zhouping; Wu, Shijia
Graphical abstract: Highlights: Dual-color paper-based aptasensor is developed for visual detection of OTA and ZEN. A hydrophobic paper substrate is made via laser printing and heating treatment. A smartphone is used to capture and analyze the fluorescent images. ZEN and OTA can be analyzed with LODs down to 0.44 ng/mL and 0.098 ng/mL. Abstract: A portable paper-based microfluidic aptasensor is established to simultaneously and visually detect zearalenone (ZEN) and ochratoxin A (OTA). The targets at the sample zone can migrate to two detection zones through dual-channels and result in green and blue fluorescence recovery. This is due to the specific recognition by a respective aptamer that destroys fluorescence resonance energy transfer (FRET) from dual-color upconversion nanoparticles (UCNPs) to Cu-TCPP nanosheets. By capturing fluorescent images and analyzing the corresponding RGB value via a smartphone, ZEN and OTA can be analyzed with limits of detection down to 0.44 ng/mL and 0.098 ng/mL in the linear ranges of 0.5–100 ng/mL and 0.1–50 ng/mL, respectively. Satisfactory recoveries are also obtained for ZEN (94.5–103.7 %) and OTA (92.2–106.8 %) in corn flour. With the advantages of simple operation, low sample consumption, and broad adaptability, this promising platform allows for the on-site detection of multiple hazards in food.